CHARACTERISTIC OF VIBRATION ON THE SHAFT WHICH IS SUPPORTED BY 2, 3, AND 4 PEDESTALS - SUBBAN MALIK (NIM : 13106015); Pembimbing Utama : Dr. Ir. Zainal Abidin, ACHMAD
Pradana [2010] has done research on the influence of pedestal stiffness to the balancing performance. The research raised a question concerning the cause of large vibrations occurred when 2 shafts were supported by two or more pedestals although they were connected by a flexible coupling. Therefore, it is necessary to find out the cause of the large vibrations of the shaft supported by two or more pedestals. This research uses the rotating shaft setup made by Pradana [2010]. The setup needs modification. The modification is intended to enable vibration measurements of a rotating shaft supported by two or more pedestals so that an investigation on the effect of addition pedestals to the vibration magnitude. Before the vibration measurement was done, it is first necessary to measure the roundness and straightness of the shafts. The roundness and straightness measurements show that four shafts being used for vibration test are not comply with the roundness and straightness of the tolerance of standard precision shafts. The rotational speed variation used during measurement is intended to determine the effect of shaft rotational speed on the vibration magnitude of the pedestals. The rotational speed variation measurement on a shaft supported by 2 and 3 pedestals showes that vibration level at 1 x rotational frequency is smaller than vibration due to natural frequency of setup. Meanwhile, a shaft supported by 4 pedestals showes that vibration level at 1 x rotational frequency is higher than vibration due to natural frequency of setup. Furthermore, additional pedestal affects the vibration level at frequency 1xRPM. The phenomenon is clearly demonstrated by the vibration level at frequency 1xRPM on shaft supported by 4 pedestals is higher than the vibration level at frequency 1xRPM on the shaft supported by 2 and 3 pedestals. The cause of the large vibration levels at frequency 1xRPM in Pedestal 2 and Pedestal 3 are not yet known.